2005
DOI: 10.1111/j.1439-0442.2005.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumour of Bone in a Cat with Extraskeletal Metastases: Pathological and Immunohistochemical Study

Abstract: A case of giant cell tumour of bone (GCTb) in the lung and in a subcutaneous mass located in the right flank, with a probable primary origin in the mid-diaphysis of the right tibia, was described in a 8-year-old female cat. Numerous multinucleated giant cells were homogeneously distributed among a population of ovoid or spindle-shaped mononuclear cells. All of them were positive for vimentin suggesting a mesenchymal origin. Spindle-shaped tumour cells resemble fibroblastic cells, showing collagen fibres in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…This is a rarely reported neoplasm in domestic animals, and few reports exist in cats. 3,7,19,23,24,26 The relative frequency of its diagnosis in the digits in this study was unexpected, as GCTB has never previously been reported in the digits of cats and is uncommon in humans. Only 13 cases of GCTB were seen in the hand in a retrospective study of 50 years of submissions at the Mayo Clinic.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This is a rarely reported neoplasm in domestic animals, and few reports exist in cats. 3,7,19,23,24,26 The relative frequency of its diagnosis in the digits in this study was unexpected, as GCTB has never previously been reported in the digits of cats and is uncommon in humans. Only 13 cases of GCTB were seen in the hand in a retrospective study of 50 years of submissions at the Mayo Clinic.…”
Section: Discussionmentioning
confidence: 54%
“…1 Typically, this tumor is reported to occur primarily in the epiphysis of tubular long bones in humans and animals, 22 and reported cases in cats originated in the femur, 24 ulna, 3,19 rib, 23 and tibia. 7 Both tumors in this study occurred in young adult cats (3 and 5 years of age); the age range in reported literature was from 1 to 12 years of age. 3,19 The histogenesis of GCTB is unclear, but the current hypothesis is that the fibroblast-like stromal cells in the tumor are the proliferating component and the giant cells that give the tumor its name are nonneoplastic reactive cells with immunohistochemical staining properties consistent with osteoclasts.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this regard, recent studies indicate that stromal spindle cells, the major component of the mononuclear cell population, are the true neoplastic elements of GCTB (Mendenhall et al 2006;Salerno et al 2008;Wülling et al 2001;Yasko 2002;Zheng et al 2001). GCTB is exceedingly rare in nonhuman species, and so far it has been only sporadically described in cats, dogs, rats, and birds (Amann et al 2007;Berg, Gliatto, and Wallace 1990;Ferreras et al 2005;Imai et al 1998;Trigo, Leathers, and Brobst 1983;Walsh and Rhodes 1995). This study aims at describing the pathological and immunohistochemical features of a GCTB-like lesion that occurred in a 71-week-old C57BL/6 female mouse harboring a Trp53 (p53) mutant allele with a G-to-A substitution at nucleotide 515.…”
mentioning
confidence: 99%
“…Both CD45 and lysozyme have been previously reported to specifically identify the MGCs populating GCTB (Aqel, Pringle, and Horton 1988;Bouropoulou, Kontogeorgos, and Manika 1985;Ferreras et al, 2005;Fornasier et al 1996;Morgan et al 2005;Roux et al 2002).…”
mentioning
confidence: 99%